Mobilizing Karbala: sonic remediations in Berlin Ashura processions. Issue 10 (9th August 2021) - McMurray, Peter
ABSTRACT: As part of their commemorations of the Battle of Karbala and martyrdom of Husayn b. 'Alī, many Muslims, especially Shi'a, participate in collective lamentation culminating on the day of Ashura, often including forms of procession in which sound plays a crucial role. In migrant communities in Berlin, Germany, such Ashura processions use sound and embodied performance not only to commemorate Husayn but also to transform or remediate urban space, creating new possibilities for community and communication, despite a variety of social and material constraints. This essay considers the role of sound in two such processions, one indoor and one outdoor, suggesting that these rituals play a key role in articulating a form of Islam unique to Berlin that also uses sound to shape Berlin as an urban space. Furthermore, these sonic and spatial remediations forge a crucial connection between Muslim Berlin and Karbala.